The Adoption of International Financial Reporting Standard (IFRS) by Ghanaian companies the level of compliance with reference to the preparation of financial statement. - Acquaye, Sandra (2016)
A Thesis submitted to the Department of Accounting and Finance, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Business Administration (Finance Option)